BiblioMaps - a software to create web-based interactive maps of science: the case of UX map - Grauwin, Sebastian; Sperano, Isabelle (My University, 2018)
Maps of science, allowing the exploration of large‐scale bibliographical datasets, are meeting an increasing interest across a broad range of audiences: students, educators, researchers, policy makers, technology developers, etc. This paper presents BiblioMaps, a freely available software that can be used to create web‐based interactive maps of science. Our toolkit uses a mixture of statistical techniques and similarity measures on bibliographic metadata extracted either from the Web of Science or Scopus. After processing, the data is used in web‐based interactive visualizations. The main visualization is a map of topical clusters ‐ gathering publications based on shared references ‐ whose characteristics can be easily explored in detail. As an example, we discuss some insights gained by exploring maps based on a corpus of about 10,000 "User Experience Design" research publications.
Keywords: map of science; interactive tool; web interface; information visualization; bibliometry; UX design